2021
DOI: 10.3390/pr9040705
|View full text |Cite
|
Sign up to set email alerts
|

A Proper Shape of the Trailing Edge Modification to Solve a Housing Damage Problem in a Gas Turbine Power Plant

Abstract: To solve the housing damage problem of a fractured compressor blade (CB) caused by an impact on the inner casing of a gas turbine in the seventh stage (from 15 stages), modifications of the trailing edge (TE) of the CB have been proposed, namely 6.5 mm curved cutting and a combination of 4 mm straight cutting with 6.5 mm curved cutting. The simulation results of the modifications in both aerodynamics variables Cl and Cd and the pressure ratio, including structural dynamics such as a normalized power spectrum, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 21 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…From the calculation based on the actual conditions at the factory, we found that the Reynolds numbers (Re) were between 5 × 10 3 -2 × 10 5 , which matched the SST k-ω turbulence model. The SST k-ω equations can be written as [6][7][8]12,25,27]:…”
Section: Sst K-ωmentioning
confidence: 99%
“…From the calculation based on the actual conditions at the factory, we found that the Reynolds numbers (Re) were between 5 × 10 3 -2 × 10 5 , which matched the SST k-ω turbulence model. The SST k-ω equations can be written as [6][7][8]12,25,27]:…”
Section: Sst K-ωmentioning
confidence: 99%